Nutrient Utilization Of Broiler Chicken Fed High Fiber Diets Supplemented With Enzyme And Yeast (Applied Biological Research, 2011)
An experiment was conducted to study the influence of enzyme and yeast  supplementation in broiler chicken fed high fiber diets. Diets comprized  of a control diet [6.2% crude fiber (CF) only] and 8.0 or 10.1% CF level  supplemented with either enzyme or yeast @ 200 g ton-1feed. No  significant effect was noticed on apparent digestibility values of crude  protein and ether extract by the addition of enzyme or yeast in treatment  groups. The CF digestion and body weight gains were significantly higher  in control and 8.0% CF + 200 g enzyme ton-1as compared to other  treatments. The results suggested that CF level can be increased upto  8.0% with enzyme supplementation without having deleterious effect in  broiler chicken.
Keywords: Broiler chicken; nutrient utilization; fiber; enzyme; yeast